FULL-STACK WEB DEVELOPMENT WITH SPRING BOOT AND ANGULAR a practical guide to building your... full-stack web application - Duldulao, Devlin Basilan (Packt Publishing, Limited, 2022)
Design, build, and deploy performant and maintainable web applications using Spring, Spring Boot, and Angular Key Features Find solutions to common problems faced while developing applications with Angular and Spring Boot Explore tips, tricks, and best practices to overcome challenges related to source code Build applications faster and more efficiently using the Spring Framework and the Spring Boot extension Book Description Angular makes building applications with the web easy and Spring Boot helps get an application up and running using just a few lines of code and minimal configuration. This book provides insights into building full-stack apps using Angular and Spring Boot effectively to reduce overall development time and increase efficiency. You'll start by setting up your CI/CD pipeline and then build your web application's backend guided by best practices. You'll then see how Spring Boot allows you to build applications faster and more efficiently by letting the Spring Framework and Spring Boot extension do the heavy lifting. The book demonstrates how to use Spring Data JPA and add its dependencies along with Postgres dependencies in the project to save or persist a user's data in a database for future use. As you advance, you'll see how to write tests and test a service using Mockito. Finally, you'll create a CI workflow or pipeline for a Spring Boot and Angular application to enable operations to deliver quality applications faster. By the end of this Spring Boot and Angular book, you'll be able to build a full-stack web application and deploy it through continuous integration and continuous deployment. What you will learn Explore how to architect Angular for enterprise-level app development Create a Spring Boot project using Spring Initializr Build RESTful APIs for enterprise-level app development Understand how using Redis for caching can improve your application's performance Discover CORS and how to add CORS policy in the Spring Boot application for better security Write tests to maintain a healthy Java Spring Boot application Implement testing and modern deployments of frontend and backend applications Who this book is for The book is for busy Java web developers and TypeScript developers with little experience developing Angular and Spring Boot apps who want to learn best practices for building full-stack web apps. Basic knowledge of HTML, CSS, and JavaScript or the Java programming language is necessary.